4CPS-113 Drug cost saving resulting from metastatic melanoma clinical trials. (March 2019) - García Moreno, FJ; González-Haba Peña, E; Sánchez Fresneda, MN; García Martín, E; García Sánchez, S; Marzal Alfaro, B; Collado Borrell, R; Mur Mur, A; Herranz Alonso, A; Sanjurjo Sáez, M
Abstract : Background: The development of checkpoint inhibitors-based immunotherapy has completely changed the therapeutic approach of metastatic melanoma (MM). In parallel, research activity concerning this tumour continues at a very high level through a large number of active industry-funded clinical trials. Purpose: To estimate the cost saving in MM therapy attributable to clinical trials (CT) in a university tertiary hospital during the period 2016–2017. Material and methods: Observational, retrospective study that took into account those CT that were financed by a sponsor. The standard therapy (ST) comparison was chosen for each trial according to the investigator's brochure and National Comprehensive Cancer Network Guidelines. The duration of ST was equated with the time of permanence of the participant in the trial. The number of days of treatment (in oral therapy) or complete cycles received (intravenous therapy) of ST were estimated. The dose of ST was established according to body surface area or weight at recruitment to trial. The costs of ST were estimated using the hospital-specific tender price on 1 January of each year. It was considered a maximum reuse of vials. Limitation: we did not consider the cost of working in aseptic conditions and the cost of administering the drugs. Results: Eleven CT reached our inclusion criteria with a total of forty-seven patients treated. The estimated cost saving per year was: €8 09 630 (2016) and €8 04 349 (2017). The therapeutic alternatives in MM that have a high budget impact are: Inmunotherapy (anti-PD1 and anti-CTLA4 antibodies). It was the ST in five CT with 34 active participants between 2016–2017. The total saving was €1, 195, 294. The amount of savings was equivalent to 99.4% of our hospital spending on immunotherapy used to treat MM between 2016–2017. Oral antineoplastic drugs (BRAF and MEK inhibitors): ST in four CT with seven active participants and a saving of €4 17 565 (equivalent to 44.2% of the spending on BRAF/MEK inhibitors during this period). Conclusion: CT using investigational medicinal products provided by the sponsor gave a considerable saving for our healthcare system within the context of clinical research and innovation. This saving has remaining constant in our study between 2016 and 2017. References and/or acknowledgements: No conflict of interest.